Seasonal effects on plasma cortisol concentrations in the Bedouin buck: circadian studies and response to ACTH. (11th August 2016) - Chergui, N.; Mormede, P.; Foury, A.; Khammar, F.; Amirat, Z.
Abstract : Our work aims at the exploration of cortisol secretion in the Bedouin goat, native to the Algerian Sahara desert, to understand the mechanisms of adaptation to extreme hot climates. In the present study, diurnal and seasonal variations of cortisol concentrations were measured in basal conditions, as well as the response to ACTH stimulation tests across seasons in bucks. The plasma concentrations of cortisol showed no diurnal cycle but a large variation across seasons. The highest levels occurred in summer and winter when the environmental conditions are at their extreme levels. The rectal temperature showed nychthemeral and seasonal variations, and BW was also different across seasons with highest values in summer and lowest in winter. The results obtained after administration of two doses (2 or 10 μg/kg BW) of synthetic ACTH to three different age groups (kids, adults and elderly animals) showed a strong increase in plasma cortisol concentrations under all conditions with maximum levels achieved between 15 and 120 min. The analysis of the area under the cortisol curve showed no significant difference between the responses to the two doses of ACTH and between age groups, but showed seasonal variations with the lowest response in autumn than in other seasons. We conclude that season significantly affects secretion of cortisol in both basal state and under ACTH stimulation. However, the variation of adrenal reactivity to ACTH is not sufficient to explain seasonal differences, and in particular the summer peak in basal circulating cortisol concentrations. Further research should focus on the respective contribution of environmental factors (such as day length, temperature, humidity) and the mechanisms involved in cortisol regulation.